Influence of fibrolytic enzymes on in vitro methane production and rumen fermentation of a substrate containing 60% of grass hay - Giraldo L.A.; Carro M.D.; Ranilla M.J.; Tejido M.L. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Batch cultures of mixed rumen microorganisms were used to study the effects of exogenous fibrolytic enzymes on the in vitro fermentation of a substrate composed by a 60:40 mixture of grass hay and concentrate. Three enzymatic preparations were tested: cellulase from Aspergillus niger (CEL), xylanase from Trichoderma viride (XYL), and a 1:1 mixture cellulase:xylanase (MIX). Samples of substrate (500 mg dry matter (DM)) were accurately weighed into 120-ml serum bottles and enzymes were added directly into the bottles at three levels: 0 (control; CON), 15 (-15) and 30 (-30) IU/g substrate DM. Bottles were kept at room temperature for 24 h before incubation with buffered rumen fluid. All enzymatic treatments, with the exception of CEL-15, increased (P<0.05) CH4 production after 6 h of incubation, but after 24 h of incubation differences (P<0.05) with control were only detected for XYL-15, XYL-30 and MIX-30. Acetate, propionate and butyrate productions at both 6 and 24 h of incubation were increased (P<0.05) by all enzymatic treatments. NH3-N concentrations, pH and gas production at 24 h of incubation were not affected (P>0.05) by the addition of enzymes. The treatment of substrate with XYL-15, MIX-15 and MIX-30 increased (P<0.05) neutral-detergent fibre degradability (61.3, 59.9 and 60.6%, respectively) compared to the control (56.5%). The results indicate that the xylanase was more effective than the cellulase in stimulating the in vitro fermentation of substrate, but for most of the measured parameters there were no differences (P>0.05) due to the level of enzymes (15 vs 30 IU/g DM).
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)